Mind your faith a student's guide to thinking & living well - Horner, David A., 1956- (Downers Grove, Ill. : IVP Academic, 2011)
David Horner restores sanity to the collegiate experience with a guide to thinking and flourishing as a Christian. Carefully exploring how ideas work, he gives students essential tools for thinking contextually, thinking logically and thinking worldviewishly. He addresses faith and reason and how to handle doubts, with an eye toward not just thinking clearly but also living faithfully and morally.
Sanity in the university : getting started -- Loving God with your mind -- The truth about truth -- The truth about belief and knowledge -- Thinking contextually : find common ground -- Thinking logically : ask good questions and give good reasons -- Thinking worldviewishly : connect the dots -- The nature of faith : getting it clear -- The necessity of faith : faith and reason -- Challenges to faith : handling doubts and objections -- The credibility of faith : thinking worldviewishly -- College life and the good life : a moral vision -- Lessons from Le Chambon : a moral example.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Thought and thinking -- Religious aspects -- Christianity; Apologetics; Universities and colleges -- Religion; Students -- Religious life; RELIGION / Christian Life / General; Electronic books